We The People: Immigration Counter-Narratives in the High School Visual Arts Classroom - Mernick, Alisha (Radical Teacher, 2021)
Immigrant students are deeply impacted by the xenophobic dominant narratives about immigration in the United States today, and are at risk of developing a deficit mindset about their own cultures. Our classrooms can serve as spaces of resistance to anti-immigrant and neo-nativist values by intentionally raising student critical consciousness about these oppressive forces, and centering our student’s lived experiences and funds of knowledge in the curriculum. This article looks at one high-school arts curriculum unit prompting students to critically analyze the dominant narratives about immigration, interview real immigrants in their lives, and create a counter-narrative art work for public display. The aim for this project was to give immigrant students a space to process, analyze, and counter the xenophobic narratives surrounding them. Summary of the unit plan, student work samples, classroom culture, and alumni testimonials are included.